The role of leaders in managing organisation boundaries - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
The paper notes the importance of the boundary concept in the organisation and management theory and practice and attempts at identifying the role of leaders in the organisation's boundary management processes. The starting point is the assumption that looking at an organisation as an open system which interacts with its environment validates a claim that an organisation's success depends on the efficiency of such interaction with the environment, taking place across boundaries, which means that boundaries are not unimportant, peripheral components of the organisation management system, but rather its critical constituents, determining the ability to correctly define the organisation's operations and behaviours of its stakeholders. This assumption required the consequent identification of the role of leadership in the boundary management processes. The paper discusses the role of leadership in the 21st century, the evolving competition paradigm, the impact of globalisation and diversity on corporate management, the role of organisational culture and management process transformation.
Keywords: zarządzanie organizacją; procesy zarządzania; zarządzanie granicami organizacji; rola przywódcy; liderzy organizacji; management processes; managing organisation's boundaries; role of leaders; leaders in organisations